Voriconazole MICs are predictive for the outcome of experimental disseminated scedosporiosis - Martin Vicente, Adela; Guarro, Josep; González González, Gloria María; Lass Flörl, Cornelia; Lackner, Michaela; Capilla, Javier (2016)
Scedosporiosis is associated with a mortality rate of up to 90% in patients suffering from disseminated infections. Recommended first-line treatment is voriconazole, but epidemiological cut-off values and clinical breakpoints have not been determined. Objectives: To correlate voriconazole treatment response in mice suffering from disseminated scedosporiosis with MIC values determined using CLSI broth microdilution, Etest (bioMe´rieux) and disc diffusion